1998
DOI: 10.1111/j.1432-2277.1998.tb01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Biliary reconstruction with or without an internal biliary stent in orthotopic liver transplantation: a prospective randomised trial

Abstract: Choledochocholedochostomy (CCD) with a 7 fr/8 fr Cotton Leung internal biliary stent removed at endoscopic retrograde cholangiography (ERC) 3 months following orthotopic liver transplantation (OLT) was the technique used on our unit for biliary reconstruction. From June 1995 to July 1996, we randomised 37 OLT patients with CCDs to receive either an internal stent (group I, rzd= 18) or no stent (group 11, n = 19). Patients in group I had an E R C at 3 months for stent removal whereas patients in group I1 had an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In our case, the common bile duct was used for the anastomosis and the anastomotic site did not have a stricture, so that the use of an internal biliary catheter to stent the anastomosis became a late-onset life threatening complication. Previous studies have reported about stent-related morbidities and mortalities (8). However, from a historical point of view, the necessity of using stents for the biliary reconstruction has been reported from many institutions because of the high incidence of complications linked to these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the common bile duct was used for the anastomosis and the anastomotic site did not have a stricture, so that the use of an internal biliary catheter to stent the anastomosis became a late-onset life threatening complication. Previous studies have reported about stent-related morbidities and mortalities (8). However, from a historical point of view, the necessity of using stents for the biliary reconstruction has been reported from many institutions because of the high incidence of complications linked to these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The use of stents can even result in a higher incidence of stenosis, not to mention further possible complications from T-tubes or endoprostheses [3]. For the treatment of biliary obstruction, short-term stenting is a simple and useful procedure that obviates the need for surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It also needs to be present for 6–12 wk after transplantation often to the patients’ discomfort. To avoid complications associated with the use of biliary drainage several authors proposed some technical modifications (173–178). Sawyer used a polypropelene drainage catheter introduced through the stump of cystic duct instead of standard T‐tube, showing significant reduction of tube‐related complications, but not the frequency of other biliary complications (174).…”
Section: Biliary Anastomosismentioning
confidence: 99%
“…Sawyer used a polypropelene drainage catheter introduced through the stump of cystic duct instead of standard T‐tube, showing significant reduction of tube‐related complications, but not the frequency of other biliary complications (174). Internal stenting was used by other authors (175, 176). Johnson recommended use of double‐J catheter as an internal stent as a safe alternative to standard T‐tube (175).…”
Section: Biliary Anastomosismentioning
confidence: 99%
See 1 more Smart Citation